Increasing Students' Creativity and Environmental Awareness Through Recycling Craft Training at Tanjungjaya Village Elementary School - yuningsih, siti hadiaty; Jaizul, Alim (International Journal of Research in Community Services, 2025)
The problem of plastic waste is an urgent environmental issue that requires early handling through an educational approach. This study aims to evaluate the effectiveness of recycling craft training in improving creativity and environmental awareness of elementary school students in Tanjungjaya Village, Panimbang District, Pandeglang Regency. The method used is descriptive qualitative with a participatory approach, involving students, teachers, and the community in the entire activity process. Data were collected through participatory observation, structured interviews, visual documentation, and pre- and post-activity questionnaires. The results of the study indicate that this training is able to develop students' creativity in processing household waste into useful craft products such as flower pots, photo frames, and educational toys. In addition, there was a significant increase in students' environmental awareness, which was reflected in the behavior of sorting waste and utilizing used goods. This activity also builds cooperation between students and strengthens the relationship between schools and the community. These findings support the importance of contextual and real-life experience-based learning in fostering environmental care characters from an early age. Therefore, recycling craft training is recommended as part of environmental-based educational innovations in elementary schools, especially in rural areas, in order to form a creative, responsible, and environmentally aware generation.